Pemupukan Npk Dan Ameliorasi Lahan Pasang Surut Sulfat Masam Berdasarkan Nilai Uji Tanah Untuk Tanaman Jagung - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
4BSTRACT One factor that limits maize growth and yield on tidal swampland is acidic sulphate soil. The marginal soil is very low in nutrient content, pH and organic mailer. Low budgeted farmers can not overcome the problem by applying higher rate of fertilizer and ameliorani. The objective of this experiment is to determine the most effective dosage of NPK and ameliorant that give the best growth and yield of maize on tidal swampland. The experiment was conducted in the farmers fields at Barambai, South Kalimantan in September 1999 - Maret 2000. Before the trial was started, survey and analysis of nutrients was conducted in the laboratory to decide the need of nutrients in the field during July -September 1999. The trial was arranged in randomized block design with three replications. Results of the soil analysis showed that the status of NPK nutrients was identified as Barambai low-low-low. Application of NPKCa as much as 200 kg/ha Urea + 125 kg/ha SP-36 + 75 kg/ha KC/ + 750 kg/ha lime provided 4,40 tlha dry grain and was significantly different from control at tidal swamp acid sulphate which has NPK nutrient status N, K and lime increase dry grain, while optimum P rate was estimated as 137,5 kg /ha of SP-36. Keywords: tidal swampland, amelioration, fertilizer, soil test value INTISARI Masalah pengembangan jagung di lahan pasang surut sulfat masam dalam program intensifikasi adalah lahan yang bersifat masam, kadar unsur hara makro rendah, serta bahan organik rendah. Pemupukan dan ameliorasi dengan dosis tinggi untuk mengatasi masalah tersebut sangat sulit diterapkan di lapangan karena rendahnya modal petani. Penelitian bertujuan untuk mengetahui dosis pupuk NPK dan amelioran yang memberikan pengaruh optimum terhadap pertumbuhan dan hasil tanaman jagung di lahan pasang surut sulfat masam. Percobaan dilaksanakan di lahan petani Barambai Kalimantan Selatan sejak Oktober 1999 hingga Maret 2000. Sebelumnya dilaksanakan survey/analisa status hara tanah sejak Juli 1999 hingga September 1999. Percobaan dilaksanakan dengan rancangan acak berblok dengan tiga ulangan dengan kombinasi perlakuan NPK dan amelioran. Status hara NPK lokasi penelitian telah diketahui, yaitu Barambai = rendah-rendah-rendah. Pemberian pupuk NPK Ca dosis 200 kg/ha Urea + 125 kg/ha SP-36 + 75 kg/ha KCI + 750 kg/ha kapur memberikan hasil jagung sebesar 4,40 t/ha yang berbeda nyata dibanding kontrol di lahan pasang surut dengan status hara NPK = rendah-rendah-rendah. Terlihat pengaruh N, K dan kapur meningkatkan hasil jagung secara liniar, sedangkan P optimum pada dosis 137,5 kg SP-36/ha.